EXPLORATION STUDY OF THE USE OF PRACTICUM TOOLSTEACHING FOR VOCATIONAL STUDYMOTORCYCLE BUSINESS ENGINEERING IN SMK - Ayuningtias, ulfa Febryani; Noor, R A M; Permana, Tatang; Mubarak, Ibnu; Gifari, Muhammad Maris Al (Journal of Mechanical Engineering Education, 2020)
This research is motivateddby the implementation of the Teaching and Learning Process (PBM) when practicing practicum, the number of students per group is relatively ideal when doing practicum comparisons of practical tools with students is (1: 1), this causes practicum to take turns so that the consequences requires a long time (over time), the rolling system and several groups waiting their turn to use some tools. Apart from that mastery learning has not been fully achieved, and timely training is not available, while students to be skilled and competent must be able to repeat themselves. This results of the competency test of the practice’sstudents that there are still many who do not pass, so they must be remedial. This study aim to determininghow the use of practical tools in the competence of Motorcycle Engineering and Business expertise in one of the State Vocational Schools in Purwakarta. The method used is descriptive method. Data collection techniques used were interviews, observation, and documentation. The results showedin general that the practical tools in the complete category were only the quantity of different tools, there were many in number and those in a few. The ratio of the use of the equipment provided to the number of students is not yet feasible between the equipment and students except for the use of personal protective equipment.